Efficient targeting of NY-ESO-1 tumor antigen to human cDC1s by lymphotactin results in cross-presentation and antigen-specific T cell expansion. Issue 4 (15th April 2022) - Le Gall, Camille; Cammarata, Anna; de Haas, Lukas; Ramos-Tomillero, Iván; Cuenca-Escalona, Jorge; Schouren, Kayleigh; Wijfjes, Zacharias; Becker, Anouk M D; Bödder, Johanna; Dölen, Yusuf; de Vries, I Jolanda M; Figdor, Carl G; et al.
Abstract : Background: Type 1 conventional dendritic cells (cDC1s) are characterized by their ability to induce potent CD8 + T cell responses. In efforts to generate novel vaccination strategies, notably against cancer, human cDC1s emerge as an ideal target to deliver antigens. cDC1s uniquely express XCR1, a seven transmembrane G protein-coupled receptor. Due to its restricted expression and endocytic nature, XCR1 represents an attractive receptor to mediate antigen-delivery to human cDC1s. Methods: To explore tumor antigen delivery to human cDC1s, we used an engineered version of XCR1-binding lymphotactin (XCL1), XCL1(CC3). Site-specific sortase-mediated transpeptidation was performed to conjugate XCL1(CC3) to an analog of the HLA-A*02:01 epitope of the cancer testis antigen New York Esophageal Squamous Cell Carcinoma-1 (NY-ESO-1). While poor epitope solubility prevented isolation of stable XCL1-antigen conjugates, incorporation of a single polyethylene glycol (PEG) chain upstream of the epitope-containing peptide enabled generation of soluble XCL1(CC3)-antigen fusion constructs. Binding and chemotactic characteristics of the XCL1-antigen conjugate, as well as its ability to induce antigen-specific CD8 + T cell activation by cDC1s, was assessed. Results: PEGylated XCL1(CC3)-antigen conjugates retained binding to XCR1, and induced cDC1 chemoattraction in vitro. The model epitope was efficiently cross-presented by human cDC1s to activate NY-ESO-1-specific CD8 + T cells. Importantly, vaccine activity was increased by targeting XCR1 at the surface of cDC1s. Conclusion: Our results present a novel strategy for the generation of targeted vaccines fused to insoluble antigens. Moreover, our data emphasize the potential of targeting XCR1 at the surface of primary human cDC1s to induce potent CD8 + T cell responses.